Parenting Styles and People Pleasing Tendencies Among Adolescents in Sidoarjo: Pola Asuh Orang Tua dan Kecenderungan People Pleaser pada Remaja di Sidoarjo - Irma Muslikhatul Khoiroh; Nurfi Laili (Psikologia : Jurnal Psikologi, 2026)
General Background: Adolescence is a critical developmental stage in which family experiences shape self-concept and interpersonal behavior. Specific Background: Parenting styles are considered an important factor in the emergence of people pleasing tendencies, characterized by excessive efforts to gain social acceptance while neglecting personal needs. Knowledge Gap: Although people pleasing behavior has received increasing attention, empirical studies examining its relationship with parenting styles among adolescents remain limited, particularly in the context of Sidoarjo. Aims: This study aimed to analyze the relationship between parenting styles and people pleasing tendencies among adolescents in Sidoarjo. Results: This quantitative correlational study involved 339 adolescents aged 13–24 years who lived with their parents. Data were collected using parenting style and people pleaser questionnaires and analyzed using Spearman’s correlation. Most respondents were in the moderate category of people pleasing tendencies (85.87%). A significant positive relationship was found between parenting styles and people pleasing tendencies (r = 0.548, p = 0.000), indicating that higher parenting scores were associated with higher people pleasing tendencies. Novelty: This study extends prior research by examining adolescents across the Sidoarjo region rather than focusing on a single school setting. Implications: The findings underscore the importance of balanced parenting practices to help adolescents develop self-respect, healthy interpersonal boundaries, and adaptive social functioning. Highlights: A majority of adolescents were classified in the moderate category of people pleasing tendencies. Parenting styles showed a significant positive correlation with people pleasing behavior (r = 0.548, p < 0.05). Balanced parental practices are essential for fostering self-respect and healthy social boundaries. Keywords: Parenting Styles, People Pleasing Tendencies, Adolescents, Family Environment, Sidoarjo